New species and records of the genus Dolophilodes Ulmer (Trichoptera: Philopotamidae) from India - Saini, Malkiat Singh; Pandher, Manpreet Singh (Zootaxa, 2011)
The genus Dolophilodes Ulmer (Trichoptera: Philopotamidae) is reviewed from India, with the description of 3 new species: D. malickyi sp. nov. and D. punjpullaensis sp. nov. from Punjpulla (Himachal Pradesh) and D. morsei sp. nov. from Lumla (Arunachal Pradesh). Dolophilodes ornatula Kimmins is reported for the first time from India. This species, D. tibetana Kimmins and D. indica Martynov are redescribed with additional collection records. A key to males of the known Indian species of this genus is provided.